Blood pressure monitoring in pregnant women at risk of developing preeclampsia - Loskutova, Tetiana; Petulko, Albina (ScienceRise: Medical Science, 2026)
The aim of research - to determine the hemodynamic patterns of preeclampsia development in pregnant women based on ambulatory blood pressure monitoring. Material and methods. A prospective cohort study included 161 women in the second half of pregnancy. The main group consisted of 77 pregnant women at risk for preeclampsia; the comparison group included 50 women with gestational hypertension; the control group consisted of 34 healthy pregnant women. Blood pressure was sampled by using a non-invasive automatic ambulatory blood pressure monitoring machine for 24h. Results. Although the average 24-hour BP is lower than the established level of 140/90 mmHg, a more detailed evaluation during ambulatory blood pressure monitoring (ABPM) in pregnant women at high risk of developing gestational hypertension and preeclampsia at the preclinical stage allows to identify following predictors: an increase systolic (SBP), diastolic (DBP), and mean arterial pressure and their amplitude; an increase the rate of the morning surge of SBP to 16.4 ± 2 and DBP to 14.5 ± 2.4 mmHg/hour; a decrease circadian index of SBP to 9.8 ± 0.64% and DBP to 7.7 ± 1%; an increase SBP variability (day/night) = 12.2 ± 0.6 / 9.77 ± 0.4 and DBP variability (day/night) = 9.1 ± 0.44 / 8.41 ± 0.45; the occurrence of elevated blood pressure episodes during the daytime (SBP up to 2.0 ± 0.53%, DBP up to 2.15 ± 0.36%) and during the nighttime period (SBP up to 5.6 ± 1.4%, DBP up to 7.85 ± 0.36%). Conclusions. ABPM allows to detect pathological hemodynamic changes (specifically isolated nocturnal hypertension and increased BP variability) at the preclinical stage. This makes the method indispensable for predicting preeclampsia and the timely adjustment of clinical management strategies for high-risk patients.